2019
DOI: 10.1200/jco.2019.37.15_suppl.9573
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil to Lymphocyte ratio (NLR): A prognostic marker in melanoma patients receiving immunotherapy.

Abstract: 9573 Background: Cancer related inflammatory processes have been shown to have an important role in tumourigenesis, disease progression, and patient prognosis. An elevated neutrophil to lymphocyte ratio (NLR) is associated with a worse outcome in several malignancies. The relationship between NLR and immune checkpoint blockade is poorly understood. We sought to investigate the role of NLR in patients receiving immune checkpoint inhibitors for metastatic melanoma (MM). We aimed to do this by comparing outcomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
1
2
1
Order By: Relevance
“…Our findings supported previous studies which reported NLR >3 as an independent prognostic factor to predict poor prognosis in melanoma 19,24–27 . Our results, however, differed from past studies which only evaluated patients who received immunotherapies, whilst our study included patients who received other treatment types, suggesting the prognostic value of NLR is not limited to immunotherapy.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Our findings supported previous studies which reported NLR >3 as an independent prognostic factor to predict poor prognosis in melanoma 19,24–27 . Our results, however, differed from past studies which only evaluated patients who received immunotherapies, whilst our study included patients who received other treatment types, suggesting the prognostic value of NLR is not limited to immunotherapy.…”
Section: Discussionsupporting
confidence: 85%
“…16,17,23 Our findings supported previous studies which reported NLR >3 as an independent prognostic factor to predict poor prognosis in melanoma. 19,[24][25][26][27] Our results, however, differed from past studies which only evaluated patients who received immunotherapies, whilst our study included patients who received other treatment types, suggesting the prognostic value of NLR is not limited to immunotherapy. Since the majority (59%) of our cases received immunotherapies, further investigation is still required to confirm the prognostic value of NLR in targeted therapies as well as other therapies.…”
Section: Discussioncontrasting
confidence: 63%
See 2 more Smart Citations